VALIDITAS PENAFSIRAN DALAM TAFSÄªR BI AL-MAâTSÅªR - Hudaya, Hairul (Jurnal Ilmiah Ilmu Ushuluddin, 2015)
There are three methods of interpretation used by commentators to interpret the Quranic verses, by riwayah, knownas tafs bi al-mats, by logic known as tafs bi al-rayi and by al-isyi. From three methods of interpretation, according to Ibn Taymiyyah, tafs bi al-mats is the best method and valid. It is based on the belief that knows themeaning of the verse is Allah, the Prophet, and his companions. In fact, the commentary by al-mats, not the wholeverse is interpreted by the Prophet, or friends but the majority carried out by commentators with ijtihadnya in placingthe Quran, Hadith and friends opinion when interpreting a verse. Thus, differences in interpretation among commentatorsbi al-mats can not be avoided. In case of Abrahams son who was sacrificed, for example, between al-Thabari, Ibn Kats and Ibn Athiyyah had different opinions and attitudes of understanding of the verses. Whiletheir interpretation is called tafs bi al-mats. Their different opinions indicate that al-tafs bi al-mats also needa review of the validity, especially related to commentators thought in placing the explanation of Quran itself,Hadith and opinion in interpreting the Quranic verses.